Data from post-tensioned reinforced and fibre reinforced concrete beams measured by Distributed Optic Fibre Sensors. Force introduction, long-term and loading to failure stages. - Fernandez, Ignasi (Chalmers University of Technology, 2025)
The dataset contains information from tests conducted on four concrete beams. The experimental program includes two main phases: a long-term monitoring phase, which evaluates time-dependent effects and post-tensioning losses, and a load-to-failure phase, where the beams are tested under a four-point bending configuration until failure.

The primary data collected consists of strain measurements obtained using Distributed Optical Fibre Sensors (DOFS) installed along the length of each beam. During the load-to-failure tests, the dataset also includes key information on the applied forces, bending moments, and the measured deflections under the jack loading points.

Datasetet innehåller information från tester som utförts på fyra betongbalkar. Försöksprogrammet består av två huvudsakliga faser: en långtidsövervakningsfas, där tidsberoende fenomen och förluster i förspänning utvärderas, samt en brottfas, där balkarna belastas till brott i en fyrpunktsböjkonfiguration.

Den huvudsakliga datainsamlingen består av töjningsmätningar med hjälp av distribuerade optiska fibergivare (DOFS) som är installerade längs balkarnas längd. Under brottfasen innehåller datasetet även viktig information om applicerade laster, böjmoment samt de uppmätta nedböjningarna vid domkraftslasterna.
Data från efterspända armerade och fiberarmerade betongbalkar uppmätta med distribuerade optiska fibersensorer. Kraftintroduktion, långtidsbeteende och belastning till brott.
Keywords: Distributed Optic Fibre Sensors; Distribuerade optiska fibergivare; Post-tensioning; förspänning; DOFS; DOFS; Civil Engineering; Samhällsbyggnadsteknik; Other Civil Engineering; Annan samhällsbyggnadsteknik